Hepatoprotective Effect of Nigella Sativa Linn (Kalajira) On Paracetamol-induced Liver Damage - Pal, Dipali Rani; Nahar, Shamusn; Roy, Kanta; Talukder, Shah Alam; Hossain, Md. Motahar; Paul, Paritosh Chandra; Eva, Eliza Omar (Bangladesh Medical Journal, 2014)
Paracetamol is the widely used non-steroidal anti-inflammatory drugs for the treatment of mild to moderate pain. It causes hepatotoxicity in therapeutic dose for prolonged time. It can induce centrilobular hepatic necrosis in large over doses. Nigella sativa (kalajira) is a medicinal plant has a protective role against hepatotoxicity. Therefore, the present study was designed to observe the protective role of Nigella sativa on paracetamol induced liver damage biochemically in Long Evans rats. The experiment was carried out in the Department of Anatomy, Dhaka Medical college, in the period of July 2003 to June 2004. Sixty matured Long Evans rats of either sex, age of 10-12 weeks and weighing between 150-200 gm were used in this study. They were divided into four equal groups. Group A was vehicle (distilled water) control group, Group B was Nigella oil treated group, Group C was paracetamol treated group and Group D was Paracetamol & Nigella sativa oil treated group. Paracetamol in a single dose of 3gm/kg body weight orally causes hepatotoxicity which was assessed bio-chemically. Nigella sativa oil at a dose of 800mg/kg body weight was administered orally for 4 weeks. It was found that significant elevation of serum alanine aminotransferase, serum aspartate aminotransferase, serum alkaline phosphatase and serum bilirubin level in paracetamol treated group. It was observed that 4 weeks oral treatment of Nigella sativa oil in Group D, decrease the level of serum alanine aminotransferase, serum aspartate aminotransferase, serum alkaline phosphatase and serum bilirubin. The result revealed that Nigella sativa oil able to give protection against paracetamol induced liver damage. However, more sophisticated biochemical studies like glutathione content and malondialdehyde level should be studied further. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18677 Bangladesh Medical Journal 2011 Vol.40(3):52-54